DELIGNIFIKASI LIMBAH AMPAS TEBU UNTUK MENDAPATKAN BAHAN BAKU CHEMICAL FLOODING DALAM EOR - dahani, wiwik (Indonesian Journal of Chemical Science, 2016)
High content of lignin provide opportunities for bagasse as a source as the source of ligninâs raw materials as to various needs. One of the use of lignin is drainage of petroleum in the reservoir, as for the EOR method. Lignin in the form of lignosulfonate surfactant is widely used because of its resistance to salinity. Lignin as a the surfactant raw materialÂ  can be obtained from bagasse delignigication process using NaOH solution extraction method. From the research that has been conducted can be shown that the concentration of NaOH used, the size of flakes bagasse and separation methods have been very influential on the acquisition of lignin. Optimum use of NaOH solution at a ratio of 1:1 weigh Â of bagasse, resultsing lignin 24 % when used in natural drying method, and 36,6 % when used method of drying with heating. The separation process by heating while providing higher yields, , it is nonetheless indicated that the physically lignin produced is not as expected. Furhter studies needs to be done to obtain lignin characteristics that match the needs of manufacturing the lignosulfonat as the compatible surfactants for EOR.